A Perception-Driven Transcale Display Scheme for Space Image Sequences - Lingling Zi; Xin Cong; Yanfei Peng; Pei Yang (Advances in Multimedia)
With the rapid development of multimedia technology, the way of obtaining high-quality motion reproduction for space targets has attracted much attention in recent years. This paper proposes a Perception-driven Transcale Display Scheme, which significantly improves the awareness of multimedia processing. This new scheme contains two important modules, transcale description based on visual saliency and perception-driven display of space image sequences. The former concentrates on describing the transcle feature of space targets, including three algorithms, attention region computing, frame rate conversion, and image resolution resizing. On this basis, the latter focuses on high-quality display of space movements under different scales, including three algorithms, namely, target trajectory computing, space transcale display, and space movement display. Extensive quantitative and qualitative experimental evaluations demonstrate the effectiveness of the proposed scheme.